2002
DOI: 10.1067/mcp.2002.121911
|View full text |Cite
|
Sign up to set email alerts
|

Effect of voriconazole on the pharmacokinetics of cyclosporine in renal transplant patients

Abstract: Mean cyclosporine AUC(tau) increased 1.7-fold in the presence of voriconazole. Therefore, when voriconazole is initiated in patients already receiving cyclosporine, it is recommended that the cyclosporine dose be halved and that blood cyclosporine concentrations be carefully monitored. When voriconazole is discontinued, blood cyclosporine concentrations should be monitored and the cyclosporine dose increased, if necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
2
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(97 citation statements)
references
References 16 publications
3
89
2
3
Order By: Relevance
“…39 An empiric dose reduction of 50% for CYA and 66% for tacrolimus has been proposed, along with close monitoring for a week after beginning and finishing treatment with voriconazole. 15,39,40 The combination of voriconazole and sirolimus is contraindicated according to product information, 41 but sirolimus doses reduced by 70-90% have been used safely in combination with voriconazole. [42][43][44] In our study, no ADE was observed in a patient administered sirolimus (3 mg) as the initial dose, followed by 1 mg every 3 days in combination with voriconazole.…”
Section: Discussionmentioning
confidence: 99%
“…39 An empiric dose reduction of 50% for CYA and 66% for tacrolimus has been proposed, along with close monitoring for a week after beginning and finishing treatment with voriconazole. 15,39,40 The combination of voriconazole and sirolimus is contraindicated according to product information, 41 but sirolimus doses reduced by 70-90% have been used safely in combination with voriconazole. [42][43][44] In our study, no ADE was observed in a patient administered sirolimus (3 mg) as the initial dose, followed by 1 mg every 3 days in combination with voriconazole.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] However, the drug interaction between voriconazole and calcineurin inhibitors has been systematically examined only in a limited number of renal transplant recipients (CsA) and in healthy subjects (tacrolimus), and documented sporadically in a few case reports. [7][8][9][10][11][12] In particular, the drug interaction between voriconazole and tacrolimus has not been systematically evaluated in patients to this date. In spite of such limited data, a uniform dose reduction of calcineurin inhibitors on initiating voriconazole (1/2 for CsA, 1/3 for tacrolimus) has been recommended by the manufacturer.…”
Section: Introductionmentioning
confidence: 99%
“…In one study coadministration of voriconazole and tacrolimus elevated trough tacrolimus levels in one liver transplant patient nearly ten-fold [100], and in another study tacrolimus levels were significantly increased 2.2-fold when coadministered with voriconazole [101]. In a study of renal transplant patients, concomitant administration of voriconazole with cyclosporine also resulted in a 1.7-fold increase in the geometric mean for cyclosporine area under the plasma concentration-time curve, so it is recommended that the cyclosporine dose be halved and levels monitored frequently [102].…”
Section: Toxicities Side Effects and Drug Interactionsmentioning
confidence: 99%